Instantaneous foveated preview for progressive Monte Carlo rendering - Matias K. Koskela; Kalle V. Immonen; Timo T. Viitanen; Pekka O. Jääskeläinen; Joonas I. Multanen; Jarmo H. Takala (Computational Visual Media, 2018)
Abstract Progressive rendering, for example Monte Carlo rendering of 360° content for virtual reality headsets, is a time-consuming task. If the 3D artist notices an error while previewing the rendering, they must return to editing mode, make the required changes, and restart rendering. We propose the use of eye-tracking-based optimization to significantly speed up previewing of the artist’s points of interest. The speed of the preview is further improved by sampling with a distribution that closely follows the experimentally measured visual acuity of the human eye, unlike the piecewise linear models used in previous work. In a comprehensive user study, the perceived convergence of our proposed method was 10 times faster than that of a conventional preview, and often appeared to be instantaneous. In addition, the participants rated the method to have only marginally more artifacts in areas where it had to start rendering from scratch, compared to conventional rendering methods that had already generated image content in those areas.